Tantangan Peran Partisipasi Politik Perempuan dalam Pilkades 2021 di Desa Golowoi Kecamatan Cibal Barat - Florentina Ndimung; Nurjanah Nonci; Barisan Barisan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Women’s political participation plays a crucial role in more accommodating and substantive decision making, specifically addressing women’s needs and promoting equality in general. Village head elections as an instrument of local democracy should provide an opportunity for women to compete for village leadership. However, in the 2021 village head election in Golowoi village, there where no female village head candidates. Women only served as voters, reflecting the low level of women’s political participation in leadership positions. This study aims to determine the factors that contribute to the lack of women running for office. This study used a qualitative descriptive approach, with data collection techniques including interviews, observation, and documentation. The result indicate that the main challenges to women’s political participation include a lack of political awareness, a patrilinear culture, a lack active support from family and community, domestic burdens, women’s lack of confidence and courage in running foe office, and the historical absence of female figures in Golowoi village. This study recommends the importance of collaboration between the village government, community leaders, an families encourage women to take on strategic roles, including running for village Head.